Perancangan Pengontrolan Overhead Crane Menggunakan Kabel dan Nirkabel Berbasis Arduino - Novriadi, Ari (Jurnal Teknologi Terpadu, 2019)
Overhead Crane is a heavy equipment which is very much found in various industries, factories, and workshops that are used to transport material. In general, controlling the Overhead Crane is operated by using a Push Button that is hung together with a cable on the top frame of the Overhead Crane. in this case, humans must also be able to maintain a distance when controlling Overhead Cranes that are working to transport memterials to avoid the use of Overhead Cranes. To provide security and comfort in the use of Overhead Cranes, the authors designed an Overhead Crane controller using Arduino based cable and wireless. The design of Overhead Crane control using a cable consists of several series of Push Button arranged in a plastic box and then hung on the side of the Girder Crane. for the input foot the Push Button is given a voltage 12 VDC, while the output of the Push Button is connected with contact points of the Relay 12 VDC to execute electrically mechanical Overhead Crane. While the Overhead Crane control design using wireless consists of several components, including: Arduino Mega 2560 which is combined with USB Host Shield. Bluetooth csr 4.0 Dongle is connected to the USB Host Shield port for data communication media between Arduino Mega 2560 with Bluetooth Joystick PlayStation 3 (PS3). The signal pin of the Relay modules is connected with Arduino Mega 2560 pins according to the program designed. Contact NO points Relay modules are connected with 12 VDC Relay point contacts to execute electrical mechanical Overhead Crane.